Discovering novel carriers for oral insulin tablets: a pharmacoinformatics approach. (1st January 2013) - Seenivasagam, R.; Hemavathi, K.; Sivakumar, G.; Niranjan, Vidya
Insulin is used medically to treat Type 1 diabetes mellitus most commonly injected subcutaneously for human beings. The realisation that insulin injections have become a part of life can be extremely harrowing for many diabetic patients. Using insulin therapeutically is not a new practice, but still delivery methods to make the process more bearable have not gained widespread prominence as of yet. Oral delivery of insulin in tablet form has always been a significant challenge for pharmaceutical researchers. This study is a prospect of oral insulin tablet through pharmacoinformatics approach.